The ethics of (not) giving back. Issue 2 (15th July 2018) - Hammett, Daniel; Jackson, Lucy; Vickers, Daniel
Abstract : Recent concerns with academic research 'giving back' and 'having impact' are encouraging the adoption of various practices through which academics are able to share research findings with host communities. While we support the laudable principles behind these efforts, in this contribution we reflect on the viability of such practices in relation to overseas, undergraduate fieldclasses. Drawing on our experiences of leading and teaching on a range of international fieldclasses, we explore the complexities of giving back and caution against a drift towards universalising such practices in specific ways. Instead we call for greater critical honesty as to the potential for fieldclasses to give back in multiple ways and the need to avoid inadvertently doing harm when seeking to engage in ethical practices.